Diffusion tensor imaging findings of patients with parkinson’s disease refractory to medical treatment - Guduk, Mustafa; Cenkeri, Halime Cevik; Yilmaz, Atilla; Uyanik, Sadik Ahmet; Atli, Eray; Oguslu, Umut; Yilmaz, Birnur; Gumus, Burcak (Annals of Medical Research, 2021)
Aim: Diffusion Tensor Imaging (DTI) findings can be useful to detect and measure neurodegeneration that is seen in Parkinson’s disease (PD). Microstructural changes in regions of the brain related with motor function are evaluated by using DTI measurements of fractional anisotropy (FA) to find out the possible role of the technique in diagnosis in patients with PD. Materials and Methods: The study includes 18 PD patients who were candidates for deep brain stimulation surgery, and 19 control group patients. DTI was performed in all cases. DTI characteristics of FA were measured in primary motor cortex (M1), supplementary motor area (SMA), inferior parietal lobule, putamen (P), globus pallidus externus (GPe) and internus (GPi), ventrolateral nucleus of thalamus (Th), substantia nigra (SN), cuneus, precuneus and cerebellar dentate nucleus (D) bilaterally. Additionally, we processed “raw” FA images and colored them according to fiber orientation to visualize STN and GPi nuclei. Results: Mean age of the control group was 59.2±13.2 (range: 31-79) years, while it was 56.7±16 (range: 42-77) years for the patient group. Mean duration of PD was 12.4±7.1 (range: 5-30) years. Study group FA values were significantly lower than the control group in all areas bilaterally (p<0.05). Additionally, FA-M1, FA-GPi and FA-GPe values were significantly lower on left side compared to right side (p<0.05). Conclusion: Decrease in FA values in all regions in the study group is thought to result from loss of nerve cells. Additionally, raw FA images that are processed, and colored in relation to fiber orientation can be useful for a better identification of STN and GPi nuclei. This type of imaging will provide a more precise anatomy necessary for surgical targeting.